PELAKSANAAN SENI LUKIS MENCAP DENGAN BAHAN ALAM UNTUK MENINGKATKAN KREATIVITAS DI TK KARTIKA 1-69 SIJUNJUNG - Yungsi Aini WulanPitri; Nur Hazizah (Universitas Islam Lamongan, 2021)
the abstract of this reasearch in the background of implementation the art of painting stamping in the kindegarten held stamping activity every week with variety of natural materials so that these activities attract children’s interest and don’t get bored in developing creativity. This study aims to get an overview of the implementation of stamping painting to increase creativity in TK Kartika 1-69 Sijunjung. Type research is descriptive research using a qualitative approach. To see how the implementation of stamping painting to increase the creativity of TK Kartika 1-69 Sijunjung. Data collection techniques used observation, interviews and documentation. Data analysis techniques follow Miles and Huberman, 1) data collection, 2) data reduction, 3) data presentation, 4) verification. While the data validation technique is a triangulation technique. The results of this study generally indicate that in the implementation of stamping painting with natural materials to increase creativity in TK Kartika 1-69 Sijunjung the teacher has prepared a Daily Learning Implementation Plan (RPPH). Activities are carried out every week as planned, the activities carried out include stamping with various natural ingredients. Furthermore, after the child has carried out the activities, teacher will evaluate by means of daily observations and assessments